Desarrollo de la ingeniería de detalle de la cámara climatizada para pruebas de equipos y materiales (2019)
The present project of research and design of the heated chamber was developed from the basic engineering and the study carried out by the Ministry of Mines and Energy, which found the need to have specialized cameras to perform tests and calibration of equipment refrigeration, which must acquire the label of energy efficiency as indicated in the Technical Regulation of Labeling - RETIQ in order to be marketed nationally. As a methodology, an analysis of the basic engineering was carried out "Design of a heated, automated chamber, with telemetry management and controlled operating conditions, for testing equipment and materials" where the state of the heated chamber design was verified and it was decided to modify parameters of the previous project, based on the current market study in Colombia; constantly supported by the Colombian Technical Standard NTC 5891 "Domestic refrigeration appliances, characteristics and test methods", the NTC 4838 "Commercial refrigeration equipment, test methods" and the NTC 5310 "". The air conditioning systems chosen in the basic project of the chamber were validated, the new design parameters of the test laboratories were established based on the capacity of refrigeration equipment destined to be evaluated and from this the engineering was carried out. detail where the new thermal load of cooling and heating was calculated for each of the rooms, the teams responsible for providing the environmental conditions required for the execution of the energy efficiency tests were selected and finally the financial costs of the project were determined by evaluating the equipment and materials for the construction of this.